Difficulties in the treatment of acne fulminans - case report - Dorota Kozłowska; Anna Baran; Iwona Flisiak (Termedia Publishing House, 2015)
Introduction. Acne fulminans is the most severe form of acne. It occurs predominantly in boys in the peripubertal period. Skin lesions are accompanied by general symptoms and laboratory abnormalities. Objective. Presentation of a patient with acne vulgaris in whom after 6 weeks of treatment with isotretinoin a rapid exacerbation of acne lesions occurred. Case report. A 38-year-old patient with a history of acne was admitted to the department due to severe symptoms of acne with associated fever, loss of weight and muscle and joint pain, which developed during isotretinoin therapy. Laboratory tests showed anemia and increased inflammatory markers. After administration of systemic glucocorticosteroids partial local improvement and regression of general symptoms were achieved. Addition of isotretinoin again caused pain of spine. After therapy with lymecycline a clinical improvement was achieved. Conclusions. Acne fulminans is a rare complication of therapy with isotretinoin. Due to the coexistence of systemic symptoms and risk of disfiguring scars, early diagnosis and introduction of appropriate treatment are required.